2020
DOI: 10.1186/s12889-020-8158-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting HBV vaccination in a Medical training College in Kenya: A mixed methods Study

Abstract: Background: Hepatitis B Virus (HBV) is highly endemic in Sub-Saharan Africa with 70 to 90% of the population becoming infected before the age of 40 years. Healthcare workers (HCWs) including healthcare students (HCSs) are at an increased risk of contracting HBV due to occupational exposure. HCSs are especially at a high risk because of their inexperience with infection control procedures and insufficient knowledge about the level of risk when dealing with patients. Despite the availability of an effective vacc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
6
11
3
1
Order By: Relevance
“… 1 However, in a previous Kenyan study, the major reason for not receiving the recommended doses was the non-availability of the vaccine. 13 In our findings, the reasons were different as the majority revealed that lack of awareness of the HBV vaccine was the greatest reason for their non-uptake of the vaccine. This finding is understandable because our present study was performed on a general antenatal (pregnant) women population while the previous Nigerian study 1 and Kenyan study 13 were on health workers.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“… 1 However, in a previous Kenyan study, the major reason for not receiving the recommended doses was the non-availability of the vaccine. 13 In our findings, the reasons were different as the majority revealed that lack of awareness of the HBV vaccine was the greatest reason for their non-uptake of the vaccine. This finding is understandable because our present study was performed on a general antenatal (pregnant) women population while the previous Nigerian study 1 and Kenyan study 13 were on health workers.…”
Section: Discussionmentioning
confidence: 57%
“…We defined HBV vaccination status as: (i) no vaccination when no dose was received; (ii) partial vaccination when one or two doses were received; and (iii) full vaccination when three or four doses were received. 13 …”
Section: Methodsmentioning
confidence: 99%
“…A similar result was observed in a study done in a Syrian private university and in a study done in Qassim University, in which students had poor knowledge about HBV but believed that medical students had a higher risk of infection contraction. [ 11 16 ] It also revealed that male students had a higher level of knowledge about HBV transmission when compared to female students. These findings are not in line with a study conducted at King Khalid University Hospital (KKUH) in Riyadh, Saudi Arabia, in which females had a higher level of knowledge than males.…”
Section: Discussionmentioning
confidence: 99%
“…A multi-centric study, remarkably similar to this one but performed on a large scale and including more than 2,000 students, was reported from Greece, which noted that the vaccination rate was more than 80% among the medical, nursing, and paramedical students [22]. In a recent study from Kenya, it was observed that although 85% of the study participants were vaccinated at least once before, only 20% of them received all required doses for complete vaccination [23].…”
Section: Knowledge and Status Of Vaccinationmentioning
confidence: 67%